CONTROL OF PACKAGING PRINT QUALITY WITH AN INTEGRATED PRODUCTION FLOW SYSTEM IN PREPRESS - Tri Cahyadi; Adi Susanto; Dwi Riyono (Kreator, 2019)
The integration of the production flow on precast is the initial requirement in determining the results that will be obtained on a graphic product, especially on the resulting color. The goal is to produce accurate prints with the processed data on a computer device. In the data process conducted using interview and observation methods. Interviews were conducted with resource persons who were experts in their fields and observations made were direct practice guided by experts. The results obtained from the data study carried out are in the form of a file format that is useful for integrating work system flows in the precast section of a graphics industry.Keywords— Control, Integrated Systems, Graphics Technology